Knotting of Urethral Catheters: a Preventable Complication - Muhammad Talat Mehmood; Muhammad Sajjad Ashraf; Talat Mehmood (Journal of the Dow University of Health Sciences, 2010)
A number of complications are associated with Urethral catheterization. Feeding tube is usually used forthis purpose in children. Spontaneous intravesical knotting of such urethral catheters is a known but rarecomplication. We are reporting two cases of intravesical knotting of feeding tube used to drain bladder inpatients who underwent urethroplasty.